2012
DOI: 10.1016/j.jtcvs.2012.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgical and ablative cure for localized sternal compression–induced cardiomyopathy and ventricular tachyarrhythmia

Abstract: FIGURE 1. A, Preprocedure electrocardiogram showing monomorphic nonsustained ventricular tachyarrhythmia with superior axis left bundle branch block morphology. B, Postprocedure electrocardiogram showing sinus rhythm and no ventricular arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Previous studies demonstrated preoperative arrhythmia showed marked improvement after surgical repair of pectus excavatum [6,7]. In addition, difficult surgical and catheter ablation were demonstrated in several reports [8,9].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated preoperative arrhythmia showed marked improvement after surgical repair of pectus excavatum [6,7]. In addition, difficult surgical and catheter ablation were demonstrated in several reports [8,9].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, DeSimone et al . reported a case of pectus excavatum associated with both non‐sustained and sustained monomorphic VT . The patient underwent catheter ablation, followed by surgical correction of the pectus excavatum.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, DeSimone et al reported a case of pectus excavatum associated with both non-sustained and sustained monomorphic VT. 7 The patient underwent catheter ablation, followed by surgical correction of the pectus excavatum. Despite apparently successful catheter ablation, the authors argued that the right ventricular compression could be a persistent source of arrhythmogenesis and hence the patient underwent surgery to correct the skeletal deformity.…”
Section: Figure 1 (A) Resting Electrocardiogram Showed An Rsr Pattermentioning
confidence: 99%
“…A variety of treatment modalities for symptomatic ventricular arrhythmias in patients with PE have been described by other case reports. 5,[11][12][13] Hamoud et al 11 cause of SCA due to a lack of available data. Therefore, it was reasonable to proceed with ICD placement post-surgical repair as secondary prevention of SCA in our patient.…”
Section: Accepted Manuscriptmentioning
confidence: 99%